Implementation of software defined radio for ground station - Kaur, Kelvinder (2017)
A ground station is a radio station which telecommunicates with the satellite in outer space by transmitting and receiving high frequency radio waves, ranging from 3 to 30GHz. Whenever a ground station and a satellite manages to transmit and receive signals, a communication link is established. This link is essential for broadcasting services, tracking, delivering commands and necessary updates and uploads to the satellite. Moreover, the ground station equipment can be supervised and controlled remotely usually by serial or networking technologies. Therefore, in this final year project, there will be four standalone models (USRP x310, USRP E312, ZC706 & AD-FMCOMM S3) which will be assembled and devised to evaluate the advantages and fall backs of each model. Through these comparisons, the model which displays high feasibility and beneficial properties, could be further represented as a standalone ground station. There are two platforms used during the testing of the models; Windows and Ubuntu. The purpose of having an array of software platforms was to bring versatility in the operation of the models. WinSCP, GNU Radio Companion, Software Development Kit, Vivado, IIO Oscilloscope were some of the methods used to conduct the transmitting and receiving tests of the models. For example, the IIO Oscilloscope displays frequency/time domain waveforms of the transmitted and received signals. The RX and TX frequency must be set to 2.4GHz to ensure communications between the device and the host computer. Moreover, a MatLab file can be created and saved into the SD card of the ZC706 for the specified waveform representation at the oscilloscope. In addition, communications between two USRPs can also be established by transmitting signals to each other wirelessly. This replicates the two satellites communicating with each other in the outer space or a communication link between the satellite and the ground station. In conclusion, the ZC706 model is the most outstanding standalone model as it can be further modified by embedding additional evaluation boards to meet specific criteria of the ground station. In this project, the AD-FMCOMMS3 is an additional evaluation board which is powered from the single FMC connector of the ZC706. High transmitting and receiving frequency bandwidth makes it more favorable for this task.